hey, this is my problem:
Expand (a+b)^0, (a+b)^1, (a+b)^2, etc
(a+b)^0 = 1
(a+b)^1 = a + b
(a+b)^2 = a^2 + 2ab + b^2
(a+b)^3 = a^3 + 3a^(2)b + 3a(b^2) + b^3
(a+b)^4 = a^4 + 4(a^3)b + 6(a^2)(b^2) + b^4
I can see how this relates to pascals triangle, im just having a bit of trouble with a couple of questions about this...
What is the sum of the powers in each term of (a+b)^n?
all i can really think of is (a+b)^n = a^n + a^(n-1)... but im not sure what comes after this.
honestly i have no idea, but i think its something like that ^
Or i could be completely wrong. (Thinking) anyway, any help would be appreciated! thanks.